The Role of Cardiac Catheterization after Cardiac Arrest - Karl B. Kern; Prashant Rao; Ahmed Harhash (Cardiovascular Innovations and Applications, 2018)
Coronary angiography after cardiac arrest is important to ascertain potential treatable causes of cardiac arrest, salvage myocardium, and potentially increase long-term survival. The cause of adult out-of-hospital cardiac arrest is typically myocardial ischemia. More than 50% of such resuscitated individuals will have an acutely occluded epicardial coronary on emergency coronary angiography. This includes three in four with ST-segment elevation and one in three without ST-segment elevation. In the latter the only reliable method of detection is coronary angiography. Numerous cohort studies, now including more than 8000 patients, have shown an association between survival and early coronary angiography and/or percutaneous coronary intervention. Public reporting of percutaneous coronary intervention 30-day mortality rates has been an impediment for extending this therapy to all resuscitated individuals who experienced out-of-hospital cardiac arrest, since current databases to do fully risk-adjust rates for this subgroup. Sincere efforts are under way to correct this situation.